Investigation of structured green-band emission and electron−phonon interactions in vertically aligned ZnO nanowires - Chen, Rui (2011)
We have investigated the green band (GB) emission from vertically aligned ZnO nanowires (NWs) prepared by vapor−liquid−solid growth technique. At low temperatures, the GB emission consists of two sets of zero phonon lines and their phonon replicas independent of the laser excitation power. Temperature-dependent photoluminescence (PL) measurement is performed at temperatures from 10 to 300 K, and the thermal evolution of peak widths and the origin of PL quenching at high temperatures are discussed in detail. The multimode Brownian oscillator model is adopted to reproduce the structured GB and to determine the Huang−Rhys factor. It is found that the two electronic transitions are strongly coupled to different LO phonon modes, and the size-dependent electron−phonon coupling strength is examined.